THE ACTS OF RACIAL DISCRIMINATION TO THE BLACKS AS SEEN IN STOCKETT’S THE HELP - Olivia Nanlohy; Olga Rorintulus; Sarah Kamagi (Journal of English Culture, Language, Literature and Education, 2021)
This study aims to determine the actions of racial discrimination committed by white people against black people in The Help. This research used qualitative method, in terms of using words or text. In conducting this research, the data are collected from primary and secondary sources. The primary source is the novel entitled The Help written by Kathryn Stockett. The second sources are some related books and articles from the internet, that are supporting this research. The result of this study is presented descriptively. As the result of this research, the researcher found that there are many actions of racial discrimination reflected in The Help. It can be seen in some several sections. First, there is a Discriminatory Law namely Jim Crow Law of the Southern United States. Second, the Discriminatory Stereotypes that the white people created about the black people such as, Blacks are dirty, Black people are Thieves, Black People as Diseases, and Black People are Dumb. And the last is the Discrimination in Public Services, that can be found in residential area, library, education, health services, voting, and public transportation.